High Volumetric Hydrogen Adsorption in a Porous Anthracene-Decorated Metal–Organic Framework - Yan, Yong (Inorg Chem, 2018)
[Image: see text] We report an unprecedented ligand-based binding domain for D(2) within a porous metal–organic framework (MOF) material as confirmed by neutron powder diffraction studies of D(2)-loaded MFM-132a. A tight pocket of 6 Å diameter is formed by the close packing of three anthracene panels, and it is here rather than the open metal sites where D(2) binds preferentially. As a result, MFM-132a shows exceptional volumetric hydrogen adsorption (52 g L(–1) at 60 bar and 77 K) and the highest density of adsorbed H(2) within its pores among all the porous materials reported to date under the same conditions. This work points to a new direction for H(2) storage in porous materials using polyaromatic ligand-based sites.